Kaum LGBT dalam Sejarah Peradaban Manusi - Muhamad Tisna Nugraha (PSGA LP2M IAIN Pontianak, 2016)
The existence of lesbian, gay, bisexual, or transgender (in Indonesia known as LGBT) has become a sexual problem ini human’s life. These minority people considerably have a sexual deviance in their life. Therefore, sometimes, they are discriminated and violated by people who dislike their existence. Eventhough, on the other side, every man has an affinity rights in Law. Besides, LGBT is not an epidemic disease in society entirely. Some of them has contributed in the historical event in the past. Thus, through this article, the writer would present the information of LGBT’s life from historical and religious perspective.